Chromothripsis drives the evolution of gene amplification in cancer - Shoshani, Ofer (Nature, 2020)
Focal chromosomal amplification is an important route to generating cancer through mediating over-expression of oncogenes(1–3) or to developing cancer therapy resistance by increasing expression of a gene whose action diminishes efficacy of an anti-cancer drug. Here we used whole-genome sequencing of clonal isolates developing chemotherapeutic resistance to identify chromothripsis as a major driver of extrachromosomal DNA (ecDNA) amplification into circular double minutes (DMs) through PARP- and DNA-PKcs-dependent mechanisms. Longitudinal analyses revealed that DMs undergo continuing structural evolution to promote increased drug tolerance through additional chromothriptic events. In-situ Hi-C sequencing is used to demonstrate that DMs preferentially tether near chromosome ends where they re-integrate when DNA damage is present. Intrachromosomal amplifications formed initially under low-level drug selection undergo continuing breakage-fusion-bridge cycles, generating >100 megabase-long amplicons that we show become trapped within interphase bridges and then shattered, producing micronuclei that mediate DM formation. Similar genome rearrangement profiles linked to localized gene amplification are identified in human cancers with acquired drug resistance or with oncogene amplifications. We propose that chromothripsis is a primary mechanism accelerating genomic DNA amplification and which enables rapid acquisition of tolerance to altered growth conditions.